Klasifikasi dan Identifikasi Material terhadap Pengendapan Wax pada Sumur Minyak - Aries Prasetyo; Sudono Sudono (JOURNAL OF APPLIED SCIENCE (JAPPS), 2020)
The problem in Indonesia, especially for piping problems are generally caused by blockages that interfere with the flow process, these blockages are formed due to the presence of scales or minerals deposited to the pipe wall. Scale formation is due to the alteration of the physical properties of the oil including pour point, viscosity or others. Many technological breakthroughs developed to overcome this problem are with the addition of hot water, the injection of chemical fluids dispersant into crude oil, which serves to lower the pour point of the crude oil that will be in production or use surfactant as inhibitors so that the inner pipe wall will be water wet which can prevent the occurrence of wax deposition on the pipe surface. In subsequent developments the researchers will review by replacing or adding pipe materials with certain materials that are able to inhibit the processing of wax deposits in the pipe walls. By classifying and identifying materials that are able to inhibit the formation of wax on the pipe, it is expected to estimate the design of the pipe string so as not to form wax deposits, such as predicting wax formed at the distance So that the material application can be optimal. Verification of data on tubing will result in supporting data for the determination of the crude oil flow rate with an Excel plot used to determine the rate of wax deposition in tubing. With some selected material is expected researchers are able to determine the best material to handle the problem of wax deposits.